Imputed Meaning: An Exploration of How Teachers Interpret Grades. (3rd July 2019) - Riley, Tasha; Ungerleider, Charles
ABSTRACT: Grading and the interpretation of grades are inextricable facets of teachers' work. Nonetheless, teachers find it challenging to explain the inferences they draw from grades and the decisions they make based upon grades. This article explores teachers' thinking about the grades assigned by their peers. This study used a think-aloud task in which 21 teachers placed 24 fictional student record cards in remedial, average, or advanced programs, based upon student grades earned from Grades 4 through 7. The teachers' responses to the task exposed the many meanings they impute to grades and the biases that their interpretations revealed, providing concrete evidence of how biases influence the decisions teachers make about students.